(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
With almost 30 years of experience with stage lighting, lighting and set designer Marisa Bentivegna reflects on her creative experiences with scenic works during the Covid-19 pandemic. In this period, the interviewee was involved in a variety of theatrical productions with different conditions and forms of production. In her report, she narrates the challenges and discoveries she experienced, where the boundaries between lighting, set design, art direction and photography becomes flexible.